Auditory Discrimination Elicited by Nonspeech and Speech Stimuli in Children With Congenital Hearing Loss. - Ying Yang; Qiong Li; Yanan Xiao; Yulu Liu; Kangning Sun; Bo Li; Qingyin Zheng (Journal of Speech, Language & Hearing Research, 2022)
Purpose: Congenital deafness not only delays auditory development but also hampers the ability to perceive nonspeech and speech signals. This study aimed to use auditory event-related potentials to explore the mismatch negativity (MMN), P3a, negative wave (Nc), and late discriminative negativity (LDN) components in children with and without hearing loss. Method: Nineteen children with normal hearing (CNH) and 17 children with hearing loss (CHL) participated in this study. Two sets of pure tones (1 kHz vs. 1.1 kHz) and lexical tones (/ba2/vs./ba4/) were used to examine the auditory discrimination process. Results: MMN could be elicited by the pure tone and the lexical tone in both groups. The MMN latency elicited by nonspeech and speech was later in CHL than in CNH. Additionally, the MMN latency induced by speech occurred later in the left than in the right hemisphere in CNH, and the MMN amplitude elicited by speech in CHL produced a discriminative deficiency compared with that in CNH. Although the P3a latency and amplitude elicited by nonspeech in CHL and CNH were not significantly different, the Nc amplitude elicited by speech performed much lower in CHL than in CNH. Furthermore, the LDN latency elicited by nonspeech was later in CHL than in CNH, and the LDN amplitude induced by speech showed higher dominance in the right hemisphere in both CNH and CHL. Conclusion: By incorporating nonspeech and speech auditory conditions, we propose using MMN, Nc, and LDN as potential indices to investigate auditory perception, memory, and discrimination.